If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 27 + 5k = -7(2k + 7) Reorder the terms: 27 + 5k = -7(7 + 2k) 27 + 5k = (7 * -7 + 2k * -7) 27 + 5k = (-49 + -14k) Solving 27 + 5k = -49 + -14k Solving for variable 'k'. Move all terms containing k to the left, all other terms to the right. Add '14k' to each side of the equation. 27 + 5k + 14k = -49 + -14k + 14k Combine like terms: 5k + 14k = 19k 27 + 19k = -49 + -14k + 14k Combine like terms: -14k + 14k = 0 27 + 19k = -49 + 0 27 + 19k = -49 Add '-27' to each side of the equation. 27 + -27 + 19k = -49 + -27 Combine like terms: 27 + -27 = 0 0 + 19k = -49 + -27 19k = -49 + -27 Combine like terms: -49 + -27 = -76 19k = -76 Divide each side by '19'. k = -4 Simplifying k = -4
| 5w-15=8w-24 | | 36.8+28= | | x+58=75 | | 4x+14y+9=0 | | 12x-28y=40 | | x-34=23 | | -38-6x=5x+8(4x+6) | | (9x+9x)/3x=6x | | 4x=-12x | | 3x+6=8x-34 | | 3x+51=102 | | 36.8=28 | | 9y-3(y-3)=27 | | -4-3x=6x-2 | | (3h+2)=(9h+4)+2(3h+2)-1 | | -4+(1/3)x=4 | | 4x-16+2x=3+6x-18 | | C-12=3 | | x-6y=13 | | (5*8-12)(4*4)= | | 2v^2+15v+29= | | 6x-12+2x=2+8x-13 | | 1/4+3/8=3/4 | | 3x-15=15-3x | | (3h+2)=(3h+2)2+2(3h+2)-1 | | (3x+2)=(3h+2)2+2(3h+2)-1 | | 5(x-6)+1=4(-1+x) | | h(t)=20-16t^2+32t | | 3(n+4)=n+18 | | 5-4(2w+1)=11w-4(11+w) | | 6w-2x+38=0 | | -2(x+4)=35-(7-4x) |